Adaptive resource allocation for reliable performance in heterogeneous distributed systems. - Hussin, Masnida; Abdullah, Azizol; K. Subramaniam, Shamala (Springer, 2013)
The rapid development of distributed systems has triggered the emergence of many new applications such as Cloud applications. Satisfaction on these systems in regards their services is an important indicator that reflect quality of IT resource management. In this paper, we address a reliability issue in the context of resource allocation that aims to improve performance of the distributed systems. We propose a heuristic scheduling by integrating different mapping and queuing strategies into allocation policy for suitably matching tasks and resources. Dynamic resource discovery and task classification are incorporated into the heuristic scheduling in pursuit of reliable decisions. Simulation experiments show that our approach achieves better response time and utilization compared to other heuristic approaches.